Pola Cemaran Bahan Kimia Di Aliran Sungai Riam Kanan Kabupaten Banjar - Munawar Raharja; Zulfikar Ali As; Sulaiman Hamzani (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2018)
Abstract: The Pattern Of Chemical Pollution In Riam Kanan River, Kabupaten Banjar. Riam Kanan river is utilized by the community for various needs, such as for households, cultivation of fish in keramba, mining of sand and coral. This research aimed to know the pattern of chemical pollution in Riam Kanan river, which was related to flow direction, pollutant source especially keramba of fish, and flow rate, with the parameters of pH, dissolved oxygen (DO) and biochemical oxygen demand (BOD). The research was conducted by observation, field measurement and laboratory examination. Water sampling was done at 8 location : The reservoir of Riam Kanan, PLTA Ir. P. M. Noor, Tambela Sari Village, Tambela Village, Awang Bangkal Village, Mandikapau Village, The Dam of Irigation Karang Intan, and Sungai Asam village with length of rivers 13.41 km. The results showed that the flow of river ranged from 15.53 to 147.72 m3/sec,. The pH of water ranged 6.13 - 6.70. DO levels ranged 2.34 - 6.95 mg/L while BOD levels ranged 1.16 - 2.91 mg/L. The utilization of river flow for keramba of fish, households activities and sand and coral excavations had affected the quality of water, especially the level of dissolved oxygen along the river flow.